Learning and adapting: the use of monitoring and evaluation in countering violent extremism: a handbook for practitioners - Dawson, Laura; Edwards, Charlie; Jeffray, Calum; Royal United Services Institute for Defence and Security Studies (Royal United Services Institute for Defence and Security Studies, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to develop a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and evaluate CVE programmes), by providing them with key terms regarding violent extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduct monitoring and evaluation (M&E) in this emerging policy field. The handbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .

Valuing peace: delivering and demonstrating mediation results - Dilemmas & options for mediators - Wadley, Ian (Mediation Practice Series, 2017)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.